Archaeoastronomical studies of the pillars complex of the Bronze Age on the Karataevo fortress - Vodolazhskaya, L.N.; Ilyukov, L.S. (Archaeoastronomy and Ancient Technologies, 2019)
The article presents the results of archaeoastronomical analysis of the pillars complex of the Bronze Age, the pillar pits of which were discovered during archaeological excavations at the Karataevskaya fortress in 2001. In the course of the study, it was found that the pillar complex was actually a small ancient astronomical proto-observatory, which could be used in the process of observing the features of the visible motion of the Sun and the Moon. With its help, it was possible to record the sunrise / sunset of the Sun and Moon in astronomically significant directions. The cult building on the fortress and the large linear part of the defensive wall of the Karataevo fortress were oriented in one of these directions - towards the southernmost sunrise of the High Moon (southern major standstill moonrise), or the most northern sunset of the High Moon (northern major standstill moonset).